Phenomenological Qualitative Methods Applied to the Analysis of Cross-Cultural Experience in Novel Educational Social Contexts - Alhazmi, Ahmed Ali; Kaufmann, Angelica (Frontiers in Psychology, 2022)
The qualitative method of phenomenology provides a theoretical tool for educational research as it allows researchers to engage in flexible activities that can describe and help to understand complex phenomena, such as various aspects of human social experience. This article explains how to apply the framework of phenomenological qualitative analysis to educational research. The discussion within this article is relevant to those researchers interested in doing cross-cultural qualitative research and in adapting phenomenological investigations to understand students' cross-cultural lived experiences in different social educational contexts.